PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY (AR) PADA MATERI CAMERA MOVEMENT KELAS XI DKV DI SMK NEGERI 2 PADANG PANJANG - Aulia Janatun Nissa; Heri Mulyono; Rini Novita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has driven the need for innovative, interactive, and contextual learning media, particularly in vocational education. Observations conducted in Grade XI Visual Communication Design (DKV) at SMK Negeri 2 Padang Panjang revealed that students experienced difficulties in understanding camera movement material due to the dominant use of lecture-based methods and limited learning media. This condition resulted in low learning motivation and insufficient conceptual understanding. This study aims to develop Augmented Reality (AR)-based learning media for camera movement material and to determine the validity and practicality of the developed media. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included two media experts, two subject-matter experts, two teachers, and 25 Grade XI DKV students. Data were collected through observation, interviews, and validity and practicality questionnaires, while data analysis used a quantitative descriptive approach. The results indicated that the AR-based learning media achieved a very high level of validity, with percentages of 92.82% from media experts and 92.29% from material experts. Furthermore, the practicality level was categorized as very practical based on teacher assessments (94.27%) and student assessments (87.67%). Therefore, AR-based learning media are feasible to be used as an interactive learning alternative to enhance students’ conceptual understanding and learning motivation in camera movement material.